Fluidodinâmica de esferas leves e bolhas em líquidos - Melo, Fabiana Regina Grandeaux de (2007)
In the present work, it was studied the ascension motion of light spheres and bubbles experimentally in Newtonian and non-Newtonian stagnated incompressible liquids in infinite field. The movement of ascension of the spheres and bubbles were monitored by a digital photographic camera (model Sony CyberShot P32). By using of a digital strobe it was possible to observe the trajectories of the spheres and bubbles. The images from th camera were processed in the Global Lab Image 2 software. The experimental runs took place in an acrylic tank which was designed to assure the absence of wall effects. In the first stage it was studied the movement of light spheres and bubbles of nitrogen in water and glycerin which are Newtonian fluids. The drag coefficient was obtained by using experimental data of velocity. Three different curves were obtained when we worked with bubbles. The first one was obtained when the characteristic dimension was the equivalent volumetric diameter. The second one was obtained by using the diameter projected on the horizontal plan for the calculation of the number of Reynolds and aspect ratio (de/dh) for the calculation of the drag coefficient. The third one was obtained by using the aspect ratio for the calculation of both, number of Reynolds and drag coefficient. KARAMANEV et al. (2005) have mentioned that a universal curve is obtained when diameter projected on the horizontal plan is used to describe the drag coefficient. In the second stage, the same procedure was used but now we worked with non- Newtonian fluids. The third stage consists of the use of a software package (FLUENT 6.3.16) to simulate the data obtained experimentally.